2022
DOI: 10.1101/2022.03.02.482662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative infection and pathogenesis of SARS-CoV-2 Omicron and Delta variants in aged and young Syrian hamsters

Abstract: Coronavirus disease 2019 continues to batter the world with the unceasing introduction of new variants of the causative virus, SARS-CoV-2. In order to understand differences in disease caused by variants of concern and to develop variant-specific vaccines, suitable small animal models are required that mimic disease progression in humans at various stages of life. In this study, we compared the dynamics of infection with two SARS-CoV-2 variants of concern (Delta and Omicron) in aged (>1 year 3 months old) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Golden Syrian hamsters (GSH) infected with SARS-CoV-2 exhibit COVID-19 pathophysiology observed in humans, making them the preferred model for understanding SARS-CoV-2 disease pathogenesis and development of antiviral drugs (8)(9)(10)(11)(12). Several studies, including ours (13), reported comparative pathogenesis of delta and omicron in the lung and systemic inflammation (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 95%
“…Golden Syrian hamsters (GSH) infected with SARS-CoV-2 exhibit COVID-19 pathophysiology observed in humans, making them the preferred model for understanding SARS-CoV-2 disease pathogenesis and development of antiviral drugs (8)(9)(10)(11)(12). Several studies, including ours (13), reported comparative pathogenesis of delta and omicron in the lung and systemic inflammation (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 95%